Evaluation of Influence of Macroeconomic Shocks on the Banking Sector of Kazakhstan - Zaitenova, Nazym Kurmashevna; Baibulekova, Leila Abdybaevna (International Journal of Economics and Financial Issues, 2016)
The study presents the indicators of the level of non-performing loans and the measure of “financial depth” of banking systems in several countries, as well as demonstrates the link between them. Further, it examines the results of the analysis of the development of banking sector and the assessment of the influence of macroeconomic factors on the sustainability of the banking sector of Kazakhstan. A mathematical model of dependence of the level of non-performing loans on macroeconomic shocks such as economic growth rates, dynamics of the national currency exchange rate, unemployment and inflation is developed. Keywords: Level of non-performing loans, financial stability monitoring system, “financial depth”, sustainability of banking sector. JEL Classifications: E51, E42